Plan de riesgos crediticios en la Cooperativa de Ahorro y Crédito Sinchi Runa ltda, provincia de Cotopaxi, cantón Saquisilí, periodo del 01 de julio al 31 de diciembre del 2016 - Iza Puco, Nancy Guillermina (2016)
This research is a Credit Risk Plan for the “Sinchi Runa” Credit Union Ltda, which aim is to improve the financial policies, so that, it may minimize or prevent defaulting and bad debts. For this research development the non-experimental methodology was used in addition to the descriptive, deductive and analytical methods; to have a better knowledge of the environment the survey and interview instruments were applied too, same that helped to identify the problems held by the institution as inadequate administration and credit risk assessment, shortcomings in the monitoring of loan portfolio. According to these results there were the need to implement a credit risk plan to help correct them by using strategies, policies, internal regulations and the use of the financial model Scoring Credit same that allow to the entity to make better assess how the profile and identification customers of potential risk events which is exposed loans and also corroborating efficiently to minimize defaulting, managing to obtain an acceptable returns in order to continue operating in the financial market and therefore the fulfilling its objectives.